Updates on the distribution and diversity of sand flies (Diptera: Psychodidae) in Romania - Cazan, Cristina Daniela; Păstrav, Ioana Raluca; Ionică, Angela Monica; Oguz, Gizem; Erisoz Kasap, Ozge; Dvorak, Vit; Halada, Petr; Dumitrache, Mirabela Oana; Volf, Petr; Alten, Bulent; Mihalca, Andrei Daniel (Parasites & vectors, 2019)
BACKGROUND: Phlebotomine sand flies (Diptera: Psychodidae) are haematophagous insects that transmit the protozoan parasite Leishmania infantum (Kinetoplastida: Trypanosomatidae), the main causative agent of both zoonotic visceral leishmaniasis (VL) and canine leishmaniasis (CanL) in the Mediterranean basin. Eight species of sand flies have been previously recorded in Romania: Phlebotomus papatasi, Phlebotomus alexandri, Phlebotomus sergenti, Phlebotomus perfiliewi, Phlebotomus neglectus, Phlebotomus longiductus, Phlebotomus balcanicus and Sergentomyia minuta. Three of them (P. perfiliewi, P. neglectus and P. balcanicus) were incriminated as vectors of L. infantum. Recent reports of autochthonous CanL in Romania require updates on sand fly distribution and diversity in this country. METHODS: Between 2013-2014 and 2016-2018, CDC light traps and mouth aspirators were used to collect sand flies in 132 locations from Romania, indoors and around various animal species shelters. Species identification of collected specimens was done using morphological keys, genetic tools and MALDI-TOF protein profiling. RESULTS: Sand flies were present in seven localities (5.3%): Eibenthal, Baia Nouă, Gura Văii (south-western Romania, Mehedinţi County); Fundătura, Pâhneşti, Epureni (eastern Romania, Vaslui County); and Schitu (southern Romania, Giurgiu County). Of the total number of collected sand flies (n = 251), 209 (83.27%) were Phlebotomus neglectus, 39 (15.53%) P. perfiliewi, 1 (0.40%) P. papatasi, 1 (0.40%) P. balcanicus and 1 (0.40%) P. sergenti (sensu lato). CONCLUSIONS: We confirmed the presence of five sand fly species previously recorded in Romania. However, their updated distribution differs from historical data. The diversity of sand fly species in Romania and their presence in areas with Mediterranean climatic influences constitutes a threat for the reemergence of vector-borne diseases. In the context of CanL and VL reemergence in Romania, but also due to imported cases of the diseases in both humans and dogs, updates on vector distribution are imperative.
Keywords: Animals; Rumunsko; Genetic Variation; Romania; Phlebotomus; Female; hmyz - vektory; zvířata; mužské pohlaví; Insect Vectors; Male; genetická variace; rozšíření zvířat; Animal Distribution; ženské pohlaví